The Occurrence of Heavy Metals in Fishers, Pekania pennanti, in Wisconsin - Sallie B. Parker; Leiel Mulakandov; Christopher J. Katz; Kent A. Hatch (Bulletin of Environmental Contamination and Toxicology, 2026)

Corrigendum to “Characterizing Influenza A Virus Lineages and Clinically Relevant Mutations Through High-Coverage Wastewater Sequencing” [Water Research (2025) Article No. 124453] - Anika John; Seju Kang; Lara Fuhrmann; Ivan Topolsky; Christopher Kent; Joshua Quick; Tanja Stadler; Timothy R. Julian; Niko Beerenwinkel (Water Research, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Characterizing influenza A virus lineages and clinically relevant mutations through high-coverage wastewater sequencing - Anika John; Seju Kang; Lara Fuhrmann; Ivan Topolsky; Christopher Kent; Joshua Quick; Tanja Stadler; Timothy R. Julian; Niko Beerenwinkel (Water Research, 2025)

Secular compositional changes in granitoids and felsic volcanics: the tectonic setting control - Kent C. Condie; Stephen J. Puetz; Christopher J. Spencer; Nick M.W. Roberts (Chemical Geology, 2025)

Magnesian-suite volcanism and ancient crust building on the Moon 4.25 billion years ago - Christopher Yen; Cécile Deligny; Bradley Jolliff; Alexander Nemchin; Paul Carpenter; Martin Whitehouse; Renaud Merle; Ryan Ogliore; Jeremy Kent; Ryan Zeigler; Juliane Gross; Scott Eckley; et al. (Earth and Planetary Science Letters, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Prioritizing US Geological Survey science on salinization and salinity in candidate and selected priority river basins - Christopher H. Conaway; Nancy T. Baker; Craig J. Brown; Christopher T. Green; Douglas B. Kent (Environmental Monitoring and Assessment, 2024)
The US Geological Survey (USGS) is selecting and prioritizing basins, known as Integrated Water Science basins, for monitoring and intensive study. Previous efforts to aid in this selection process include a scientifically defensible and quantitative assessment of basins facing human-caused water resource challenges (Van Metre et al. in Environmental Monitoring and Assessment , 192 (7), 458 2020). In the present work, we explore this ranking process based on water quality considerations, specifically salinity and salinization. We selected top candidate basins to study salinity and salinization issues in 18 hydrologic regions that include 163 candidate basins. Our prioritization is based on quantitative assessment of sources of salinity, drivers of change, and receptors that must respond to those sources and drivers. Source terms represented in the prioritization include geology, depth to brackish groundwater, stream conductivity, chloride in precipitation, urban and agricultural land use, application of road salt as a deicer, and irrigation. Drivers represented in prioritization include changes in chemical weathering as a result of changes in rainwater chemistry. Receptors include measures of water stress, measurements of stream ecological health, and socioeconomic factors. In addition, we present research activities for the USGS on salinity and salinization that can be pursued in these basins including assessment of sources, pathways, and loadings; predicting and understanding changes in sources, peaks, and trends; understanding the components of salinity and mobilization of contaminants; understanding the relationship between salinization and changing ecosystems; and developing knowledge on the causes and distribution of groundwater salinity, brackish water resources, and challenges related to desalination.

Geographic bias effects on interpretations of secular trends of Hf isotope times series in zircons - Kent C. Condie; Stephen J. Puetz; Kurt E. Sundell; Sergei A. Pisarevsky; Christopher J. Spencer; Nick M.W. Roberts (Lithos, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Diverse source materials contributed to a secular increase in δ18O for the Paleo-Mesoproterozoic A2-type granites - Gui-Mei Lu; Yi-Gang Xu; Wei Wang; Christopher J. Spencer; Nick M.W. Roberts; Kent C. Condie (Earth and Planetary Science Letters, 2024)

Four billion years of secular compositional change in granitoids - Kent C. Condie; Stephen J. Puetz; Christopher J. Spencer; Nick M.W. Roberts (Chemical Geology, 2024)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

A-type granites in space and time: Relationship to the supercontinent cycle and mantle events - Kent C. Condie; Sergei A. Pisarevsky; Stephen J. Puetz; Nick M.W. Roberts; Christopher J. Spencer (Earth and Planetary Science Letters, 2023)

Ambitious subsidy reform by the WTO presents opportunities for ocean health restoration - Christopher Costello; Katherine Millage; Sabrina Eisenbarth; Elsa Galarza; Gakushi Ishimura; Laura Lea Rubino; Vienna Saccomanno; U. Rashid Sumaila; Kent Strauss (Sustainability Science, 2021)
The World Trade Organization (WTO) is in a unique position to deliver on Sustainable Development Goal (SDG) 14.6 by reforming global fisheries subsidies in 2020. Yet, a number of unanswered questions threaten to inhibit WTO delegates from crafting a smart agreement that improves global fisheries health. We combine global data on industrial fishing activity, subsidies, and stock assessments to show that: (1) subsidies prop up fishing effort all across the world’s ocean and (2) larger subsidies tend to occur in fisheries that are poorly managed. When combined, this evidence suggests that subsidy reform could have geographically-extensive consequences for many of the world’s largest fisheries. While much work remains to establish causality and make quantitative predictions, this evidence informs the rapidly-evolving policy debate and we conclude with actionable policy suggestions.

Correction to: Ambitious subsidy reform by the WTO presents opportunities for ocean health restoration - Christopher Costello; Katherine Millage; Sabrina Eisenbarth; Elsa Galarza; Gakushi Ishimura; Laura Lea Rubino; Vienna Saccomanno; U. Rashid Sumaila; Kent Strauss (Sustainability Science, 2021)
The original article can be found online.

Position-Specific Circumstances of Concussions in the NFL: Toward the Development of Position-Specific Helmets - David J. Lessley; Richard W. Kent; Joseph M. Cormier; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Patterns of blood mercury variation in two long-distance migratory thrushes on Mount Mansfield, Vermont - Christopher C. Rimmer; John D. Lloyd; Kent P. McFarland; David C. Evers; Oksana P. Lane (Ecotoxicology, 2020)

Evidence for population genetic structure in two exploited Mekong River fishes across a natural riverine barrier - Ellen E. Biesack; Binh T. Dang; Amanda S. Ackiss; Christopher E. Bird; Phen Chheng; Latsamy Phounvisouk; Oanh T. Truong; Kent E. Carpenter (Journal of Fish Biology, 2020)
Impacts of urban development on aquatic populations are often complex and difficult to ascertain, but population genetic analysis has allowed researchers to monitor and estimate gene flow in the context of existing and future hydroelectric projects. The Lower Mekong Basin is undergoing rapid hydroelectric development with around 50 completed and under‐construction dams and 95 planned dams. The authors investigated the baseline genetic diversity of two exploited migratory fishes, the mud carp Henicorhynchus lobatus (five locations), and the rat‐faced pangasiid catfish, Helicophagus leptorhynchus (two locations), in the Lower Mekong Basin using the genomic double digest restriction site‐associated DNA (ddRAD) sequencing method. In both species, fish sampled upstream of Khone Falls were differentiated from those collected at other sites, and N e estimates at the site above the falls were lower than those at other sites. This was the first study to utilize thousands of RAD‐generated single nucleotide polymorphisms to indicate that the Mekong's Khone Falls are a potential barrier to gene flow for these two moderately migratory species. The recent completion of the Don Sahong dam across one of the only channels for migratory fishes through Khone Falls may further exacerbate signatures of isolation and continue to disrupt the migration patterns of regionally vital food fishes. In addition, H. lobatus populations downstream of Khone Falls, including the 3S Basin and Tonle Sap system, displayed robust connectivity. Potential obstruction of migration pathways between these river systems resulting from future dam construction may limit dispersal, which has led to elevated inbreeding rates and even local extirpation in other fragmented riverine species.

The unaddressed threat of invasive animals in U.S. National Parks - Ashley A. Dayer; Kent H. Redford; Karl J. Campbell; Christopher R. Dickman; Rebecca S. Epanchin-Niell; Edwin D. Grosholz; David E. Hallac; Elaine F. Leslie; Leslie A. Richardson; Mark W. Schwartz (Biological Invasions, 2020)

Artificial structure density predicts fouling community diversity on settlement panels - Kent Susick; Christopher Scianni; Joshua A. Mackie (Biological Invasions, 2020)

Further evaluation of the efficacy of emamectin benzoate for treating Pseudocapillaria tomentosa (Dujardin 1843) in zebrafish Danio rerio (Hamilton 1822) - Michael L. Kent; Virginia Watral; Christopher A. Gaulke; Thomas J. Sharpton (Journal of Fish Diseases, 2019)
Pseudocapillaria tomentosa is a pathogenic nematode parasite, causing emaciation and severe inflammatory lesions in the intestines in zebrafish Danio rerio (Hamilton 1822). Emamectin benzoate is commercially available analogue of ivermectin used for treating salmon for sea lice, under the brand name SLICE ® , and we have used this for treating zebrafish with the P. tomentosa . Here, SLICE ® , 0.2 per cent active emamectin benzoate, was used for oral treatments at 0.35 mg emamectin benzoate/kg fish/day for 14 days starting at 7 days post‐exposure (dpe). Another experiment entailed initiating treatment during clinical disease (starting at 28 dpe). Early treatment was very effective, but delaying treatment was less so, presumably due to inappetence in clinically affected fish. We evaluated emamectin benzoate delivered in water, using Lice‐Solve™ (mectinsol; 1.4% active emamectin benzoate) in two experiments. Application of four 24‐hr treatments, space over 7 days was initiated at 28 dpe at either 0.168 or 0.56 mg emamectin benzoate/L/bath, and both treatments completely eradicated infections. This was 3 or 10 times manufacture's recommended dose, but was not associated with clinical or histological side effects.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Long Evans rat spermatogonial lines are effective germline vectors for transgenic rat production - F. Kent Hamra; Christopher T. Richie; Brandon K. Harvey (Transgenic Research, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Lipid metabolites in seeds of diverse Gossypium accessions: molecular identification of a high oleic mutant allele - Drew Sturtevant; Patrick Horn; Christopher Kennedy; Lori Hinze; Richard Percy; Kent Chapman (Planta, 2017)

A mouse model of the 15q13.3 microdeletion syndrome shows prefrontal neurophysiological dysfunctions and attentional impairment - Simon R. O. Nilsson; Pau Celada; Kim Fejgin; Jonas Thelin; Jacob Nielsen; Noemí Santana; Christopher J. Heath; Peter H. Larsen; Vibeke Nielsen; Brianne A. Kent; Lisa M. Saksida; Tine B. Stensbøl; et al. (Psychopharmacology, 2016)

Elevated carbon dioxide accelerates the spatial turnover of soil microbial communities - Ye Deng; Zhili He; Jinbo Xiong; Hao Yu; Meiying Xu; Sarah E. Hobbie; Peter B. Reich; Christopher W. Schadt; Angela Kent; Elise Pendall; Matthew Wallenstein; Jizhong Zhou (Global Change Biology, 2016)
Although elevated CO 2 ( eCO 2 ) significantly affects the α ‐diversity, composition, function, interaction and dynamics of soil microbial communities at the local scale, little is known about eCO 2 impacts on the geographic distribution of micro‐organisms regionally or globally. Here, we examined the β ‐diversity of 110 soil microbial communities across six free air CO 2 enrichment ( FACE ) experimental sites using a high‐throughput functional gene array. The β ‐diversity of soil microbial communities was significantly ( P CO 2 conditions, but declined significantly ( P eCO 2 with a slope of −0.0250 than at ambient CO 2 ( aCO 2 ) with a slope of −0.0231 although it varied within each individual site, indicating that the spatial turnover rate of soil microbial communities was accelerated under eCO 2 at a larger geographic scale (e.g. regionally). Both distance and soil properties significantly ( P β ‐diversity. This study provides new hypotheses for further understanding their assembly mechanisms that may be especially important as global CO 2 continues to increase.

Erratum to: The role of the dorsal hippocampus in two versions of the touchscreen automated paired associates learning (PAL) task for mice - Chi Hun Kim; Christopher J. Heath; Brianne A. Kent; Alexa E. Horner; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

The role of the dorsal hippocampus in two versions of the touchscreen automated paired associates learning (PAL) task for mice - Chi Hun Kim; Christopher J. Heath; Brianne A. Kent; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Switching Responses: Spatial and Temporal Regulators of Axon Guidance - Andrew Kaplan; Christopher B. Kent; Frédéric Charron; Alyson E. Fournier (Molecular Neurobiology, 2014)

Interactions between specific phytoplankton and bacteria affect lake bacterial community succession - Sara F. Paver; Kevin R. Hayek; Kelsey A. Gano; Jennie R. Fagen; Christopher T. Brown; Austin G. Davis‐Richardson; David B. Crabb; Richard Rosario‐Passapera; Adriana Giongo; Eric W. Triplett; Angela D. Kent (Environmental Microbiology, 2013)
Summary Time‐series observations and a phytoplankton manipulation experiment were combined to test the hypothesis that phytoplankton succession effects changes in bacterial community composition. Three humic lakes were sampled weekly M ay– A ugust and correlations between relative abundances of specific phytoplankton and bacterial operational taxonomic units ( OTUs ) in each time series were determined. To experimentally characterize the influence of phytoplankton, bacteria from each lake were incubated with phytoplankton from one of the three lakes or no phytoplankton. Following incubation, variation in bacterial community composition explained by phytoplankton treatment increased 65%, while the variation explained by bacterial source decreased 64%. Free‐living bacteria explained, on average, over 60% of the difference between phytoplankton and corresponding no‐phytoplankton control treatments. Fourteen out of the 101 bacterial OTUs that exhibited positively correlated patterns of abundance with specific algal populations in time‐series observations were enriched in mesocosms following incubation with phytoplankton, and one out of 59 negatively correlated bacterial OTUs was depleted in phytoplankton treatments. Bacterial genera enriched in mesocosms containing specific phytoplankton assemblages included L imnohabitans (clade betI ‐ A ), B dellovibrio and M itsuaria . These results suggest that effects of phytoplankton on certain bacterial populations, including bacteria tracking seasonal changes in algal‐derived organic matter, result in correlations between algal and bacterial community dynamics.

Mercury concentrations in tropical resident and migrant songbirds on Hispaniola - Jason M. Townsend; Christopher C. Rimmer; Charles T. Driscoll; Kent P. McFarland; Eduardo Iñigo-Elias (Ecotoxicology, 2013)

Mass Psychogenic Illness: Psychological Predisposition and Iatrogenic Pseudo-vocal Cord Dysfunction and Pseudo-reactive Airways Disease Syndrome - Herman Staudenmayer; Kent L. Christopher; Lawrence Repsher; Ronald H. Hill (Journal of Medical Toxicology, 2011)

Two putative histidine kinases are required for cyst formation in Rhodospirillum Centenum - Neena Din; Charles J. Shoemaker; Kent L. Akin; Christopher Frederick; Terry H. Bird (Archives of Microbiology, 2011)

Mercury bioaccumulation and trophic transfer in the terrestrial food web of a montane forest - Christopher C. Rimmer; Eric K. Miller; Kent P. McFarland; Robert J. Taylor; Steven D. Faccio (Ecotoxicology, 2010)

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

Mercury Concentrations in Bicknell?s Thrush and Other Insectivorous Passerines in Montane Forests of Northeastern North America - Christopher C. Rimmer; Kent P. McFarland; David C. Evers; Eric K. Miller; Yves Aubry; Daniel Busby; Robert J. Taylor (Ecotoxicology, 2005)

AM404 and VDM 11 non-specifically inhibit C6 glioma cell proliferation at concentrations used to block the cellular accumulation of the endocannabinoid anandamide - Kent-Olov Jonsson; Anna Andersson; Stig O. P. Jacobsson; Séverine Vandevoorde; Didier M. Lambert; Christopher J. Fowler (Archives of Toxicology, 2003)

Nucleic acid vaccines - Brent S. McKenzie; Alexandra J. Corbett; Jamie L. Brady; Christopher M. Dyer; Richard A. Strugnell; Stephen J. Kent; David R. Kramer; Jefferey S. Boyle; Andrew M. Lew (Immunologic Research, 2001)

Iron fertilization and the Trichodesmiumresponse on the West Florida shelf - Jason M. Lenes; Brian P. Darrow; Christopher Cattrall; Cynthia A. Heil; Michael Callahan; Gabriel A. Vargo; Robert H. Byrne; Joseph M. Prospero; David E. Bates; Kent A. Fanning; John J. Walsh (Limnology and Oceanography, 2001)
Prior laboratory studies of Trichodesmium have shown a high iron requirement that is consistent with the biochemical demand for iron in the enzyme nitrogenase. Summer delivery of iron, in the form of Saharan dust, may provide an explanation for Trichodesmium blooms observed in offshore waters of the West Florida shelf over the last 50 yr. During ecology and oceanography of harmful algal blooms (ECOHAB) field studies, background iron levels (0.1–0.5 nmol kg −1 ) were found at the surface during periods of minimal dust delivery (May 2000 and October 1999). In contrast, total dissolved iron concentrations on the order of ∼16 nmol kg −1 were measured at the West Florida shelfߚbreak after a July 1999 Saharan dust event that was identified by advanced very high resolution radiometer (AVHRR) imagery, groundߚbased radiometers, air mass analysis, and aerosol samples (dust and nonߚseaߚsalt nitrate) collected throughout South Florida. The Trichodesmium response following this July dust event was a 100–fold increase over background biomass, reaching a surface stock of ∼20 colonies L −1 . Surface dissolved concentrations of both inorganic and organic phosphorus decreased below detectable limits during this bloom. Dissolved organic nitrogen concentrations associated with the bloom (15–20 µM) were 3–4–fold greater than background and much larger than ambient NO 3 − concentrations ( −1 ). If all dissolved organic nitrogen (DON) is converted to urea and ammonium, this organic nitrogen could have supported the red tide of >20 µg chl L −1 of the toxic dinoflagellate, Gymnodinium breve , found along the West Florida coast during October 1999.

Neurotoxicity of glutamate in chick telencephalon neurons: reduction of toxicity by preincubation with carbachol, but not by the endogenous fatty acid amides anandamide and palmitoylethanolamide - Mikael Andersson; Stig O. P. Jacobsson; Kent-Olov Jonsson; Gunnar Tiger; Christopher J. Fowler (Archives of Toxicology, 2000)

The complete primary structure of mouse 20S proteasomes - Laura A. Elenich; D. Nandi; A. Elizabeth Kent; T. Scott McCluskey; M. Cruz; Mohan N. Iyer; Elaine C. Woodward; Christopher W. Conn; Amber L. Ochoa; David B. Ginsburg; J. J. Monaco (Immunogenetics, 1999)